Item analysis as tool to validate multiple choice question bank in pharmacology - Date, Amit P.; Borkar, Archana S.; Badwaik, Rupesh T.; Siddiqui, Riaz A.; Shende, Tanaji R.; Dashputra, Amruta V. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Multiple choice questions (MCQs) are a common method for formative and summative assessment of medical students. Item analysis enables identifying good MCQs based on difficulty index (DIF I), discrimination index (DI), distracter efficiency (DE). The objective of this study was to assess the quality of MCQs currently in use in pharmacology by item analysis and develop a MCQ bank with quality items. Methods: This cross-sectional study was conducted in 148 second year MBBS students at NKP Salve institute of medical sciences from January 2018 to August 2018. Forty MCQs twenty each from the two term examination of pharmacology were taken for item analysis A correct response to an item was awarded one mark and each incorrect response was awarded zero. Each item was analyzed using Microsoft excel sheet for three parameters such as DIF I, DI, and DE. Results: In present study mean and standard deviation (SD) for Difficulty index (%) Discrimination index (%) and Distractor efficiency (%) were 64.54±19.63, 0.26±0.16 and 66.54±34.59 respectively. Out of 40 items large number of MCQs has acceptable level of DIF (70%) and good in discriminating higher and lower ability students DI (77.5%). Distractor efficiency related to presence of zero or 1 non-functional distrator (NFD) is 80%. Conclusions: The study showed that item analysis is a valid tool to identify quality items which regularly incorporated can help to develop a very useful, valid and a reliable question bank.